PENGARUH BAURAN PEMASARAN JASA PENDIDIKAN TERHADAP TINGKAT KEPUASAN SISWA PADA SMA PGRI KURNIA GARUT - Yokeu Bernardin, Deden Edwar (LPPM Universitas BSI, 2013)
ABSTRACT Â -Â The research wasconductedat theHigh SchoolMain Page PGRI Kurnia,effortto give satisfaction tothe students, using the toolsisthe marketing mix.Where the marketing mixconsists ofproduct, price, place, promotion, people, physical evidence and process. Base donthe background, andthe phenomenon exists, the author sconducteda study todetermine how much influence marketing mixto the level ofstudent satisfactionon the school PGRI Garut Kurnia either simulta neouslyor partially. Elements ofthe marketing mixwhichmost influence onstudent satisfaction. The research method used path analysis with the help of SPSS17. 0 software. The study was conductedon 72 respondent sintheentire high school students PGRI Kurnia Garut, chosen at random. The influence ofthe marketing mix21.60% (coefficient of determination R20.216), while the other factorsof 78.40%. While partial three of seven independent variables, theelements ofthe marketing mixthat providesthe greatest influence ofthe biggestis the promotion with determination coefficient0.281; pricewith a coefficient of0.254, and the process of the coefficient 0.244.Keywords: marketing mix, satisfaction